Smart home energy management system using renewable energy - Mitra, Nilam Sanjib; Arnob, Chowdhury Zahirul Islam; Saad, Adnan Bin Hashem; Alam, Md. Taohidul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.